Thermal load at workstations in the underground coal mining: Results of research carried out in 6 coal mines - Krzysztof Słota; Zbigniew Słota; Ewa Kułagowska (Nofer Institute of Occupational Medicine, 2016)
Background: Statistics shows that almost half of Polish extraction in underground mines takes place at workstations where temperature exceeds 28°C. The number of employees working in such conditions is gradually increasing, therefore, the problem of safety and health protection is still growing. Material and Methods: In the present study we assessed the heat load of employees at different workstations in the mining industry, taking into account current thermal conditions and work costs. The evaluation of energy cost of work was carried out in 6 coal mines. A total of 221 miners employed at different workstations were assessed. Individual groups of miners were characterized and thermal safety of the miners was assessed relying on thermal discomfort index. Results: The results of this study indicate considerable differences in the durations of analyzed work processes at individual workstations. The highest average energy cost was noted during the work performed in the forehead. The lowest value was found in the auxiliary staff. The calculated index of discomfort clearly indicated numerous situations in which the admissible range of thermal load exceeded the parameters of thermal load safe for human health. It should be noted that the values of average labor cost fall within the upper, albeit admissible, limits of thermal load. Conclusions: The results of the study indicate that in some cases work in mining is performed in conditions of thermal discomfort. Due to high variability and complexity of work conditions it becomes necessary to verify the workers' load at different workstations, which largely depends on the environmental conditions and work organization, as well as on the performance of workers themselves. Med Pr 2016;67(4):477-498